Cyberlaw and Adolescent Behavior: A Comprehensive Analysis - Sari, Anggi Dwi Puspita; Purwaningsih, Sri Budi; Fiddina, Irta (Proceedings of The ICECRS, 2023)
This data article presents a meticulous analysis of 4,126 journal articles sourced from the Lens.org database, focusing on the convergence of cyber law and adolescent behavior. Filtering from an initial 35,238 records, it unveils dominant themes like psychology and Poison Control studies, showcasing contributions from renowned authors and institutions like Elizabeth Cauffman and the University of South Florida. The dataset, spanning years up to 2020, highlights global interest and identifies top publishers like Springer Nature, Elsevier, and Wiley. Scatter plot analyses illustrate varying citation impacts, emphasizing the crucial role of cyber law in addressing adolescent behavior in the digital sphere, urging continuous exploration and policy evolution. Highlights : In-depth analysis of 4,126 journal articles linking cyber law and adolescent behavior. Unveiling dominant themes like psychology and notable contributors. Emphasizing the global interest and urging policy evolution in the digital realm. Keywords: Cyberlaw, Adolescent Behavior, Scholarly Works, Digital Realm, Policy Development